2020
DOI: 10.1101/2020.10.29.360412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional response to host chemical cues underpins expansion of host range in a fungal plant pathogen lineage

Abstract: The host range of parasites is an important factor in assessing the dynamics of disease epidemics. The evolution of pathogens to accommodate new hosts may lead to host range expansion, a process the molecular bases of which are largely enigmatic. The fungus Sclerotinia sclerotiorum parasitizes more than 400 plant species from diverse eudicot families while its close relative, S. trifoliorum, is restricted to plants from the Fabaceae family. We analyzed S. sclerotiorum global transcriptome reprogramming on host… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 94 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…This runs contrary to many necrotrophic pathosystems in which we expect the pathogen to contend with increasingly lignified plant material and a greater concentration of monolignols over the progression of infection (Huang et al, 2019; Mwape et al, 2021; Westrick et al, 2019). To assess the relative importance of AOX within a specific pathogen across multiple hosts, we additionally evaluated the expression of SsAOX during the infection of six distinct hosts from publicly available transcriptomic data (Kusch et al, 2021). On all hosts SsAOX was found to be up‐regulated between 200‐ and 5000‐fold when compared to an in vitro control, suggesting that SsAOX is highly expressed during infection in a nonhost‐specific manner (Kusch et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This runs contrary to many necrotrophic pathosystems in which we expect the pathogen to contend with increasingly lignified plant material and a greater concentration of monolignols over the progression of infection (Huang et al, 2019; Mwape et al, 2021; Westrick et al, 2019). To assess the relative importance of AOX within a specific pathogen across multiple hosts, we additionally evaluated the expression of SsAOX during the infection of six distinct hosts from publicly available transcriptomic data (Kusch et al, 2021). On all hosts SsAOX was found to be up‐regulated between 200‐ and 5000‐fold when compared to an in vitro control, suggesting that SsAOX is highly expressed during infection in a nonhost‐specific manner (Kusch et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the relative importance of AOX within a specific pathogen across multiple hosts, we additionally evaluated the expression of SsAOX during the infection of six distinct hosts from publicly available transcriptomic data (Kusch et al, 2021). On all hosts SsAOX was found to be up‐regulated between 200‐ and 5000‐fold when compared to an in vitro control, suggesting that SsAOX is highly expressed during infection in a nonhost‐specific manner (Kusch et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Several of these genes contained domains linked with metabolism and efflux of xenobiotic compounds, such as cytochrome P450, major facilitator superfamily, and tannase domains. Echoing these findings, Kusch et al (2022) showed that colonization of distinct host species led to a specific signature of cytochrome P450 induction. This was in line with a wider observation that infection of different host species induces different transcriptional programmes in S. sclerotiorum .…”
Section: The Parasitic Toolkit Of S Sclerotiorummentioning
confidence: 89%
“…A good starting place for this kind of research would be sequencing and comparison of the complete genomes of these species, which could determine which genes are shared and unique and whether this correlates with host preference or other lifestyle attributes, although only one study so far has used this approach. Kusch et al (2022) showed that 67.2% of the S. trifoliorum genome was syntenic with that of S. sclerotiorum . Out of the 10,626 genes predicted in the S .…”
Section: The Extraordinarily Broad Host‐range Of S Sclerotiorummentioning
confidence: 99%
See 1 more Smart Citation